2015
DOI: 10.1002/2014gl062543
|View full text |Cite
|
Sign up to set email alerts
|

Small‐scale variability patterns of DMS and phytoplankton in surface waters of the tropical and subtropical Atlantic, Indian, and Pacific Oceans

Abstract: High-resolution surface measurements of dimethylsulfide (DMS), chlorophyll a fluorescence, and the efficiency of photosystem II were conducted together with temperature and salinity along five eastward sections in the tropical and subtropical Atlantic, Indian, and Pacific Oceans. Analysis of variability length scales revealed that much of the variability in DMS concentrations occurs at scales between 15 and 50 km, that is, at the lower edge of mesoscale dynamics, decreasing with latitude and productivity. DMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 41 publications
2
37
1
Order By: Relevance
“…The results highlight the causes of spatial/temporal variability5462 and its importance for understanding ecological processes and ocean/atmosphere fluxes of biogenic gases.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The results highlight the causes of spatial/temporal variability5462 and its importance for understanding ecological processes and ocean/atmosphere fluxes of biogenic gases.…”
Section: Discussionmentioning
confidence: 90%
“…As shown in Supplementary Table S3, DMSPt consumption rates -which account for grazing-induced DMSPt loss17 - showed pronounced day vs. night differences in May but not in September. All in all, the corollary is that there is not such a thing as a universal diel pattern in DMS concentrations, as a recent circumnavigation study has concluded using a different approach54.…”
Section: Discussionmentioning
confidence: 96%
“…We calculated sea-air DMS fluxes from DMS concentration data and surface wind speeds using the gas transfer parameterization of Sweeney et al (2007) and the Schmidt number formulation of Saltzman et al (1993). Wind speed data for flux calculations were obtained from the National Centers for Environmental Prediction/National Center for Atmospheric Research (NCEP/NCAR) reanalysis data set (https://www.esrl.noaa.gov/psd/data/gridded/data.…”
Section: Ancillary Measurementsmentioning
confidence: 99%
“…Gridded monthly climatologies (Kettle et al, 1999;Lana et al, 2011) calculated from this dataset are the standard DMS product used as input to atmospheric chemistry and climate models, hence emphasizing the seasonal climatological view (Mahajan et al, 2015;McCoy et al, 2015). At the other end, the climatic role of DMS is often evaluated through extreme sensitivity tests that examine the response of Earth system models to order-of-magnitude perturbations of DMS emission (e.g., Grandey and Wang, 2015).…”
Section: Introductionmentioning
confidence: 99%